Exploring factors that influence teleworkers in the search for work-family balance - Othman, Nafishah; Ibrahim, Huda; Sheik Osman, Wan Rozaini; Mohd Yusof, Shafiz Affendi; Md Yussop, Yussalita (2011)
The purpose of this paper is to present the factors that influence teleworkers in managing border between work and family in order to attain balance.By understanding the individuals characteristics may help telewokers in balancing their work and home life.The study used the qualitative method by focusing on a single case study.Three types of techniques in collecting data were used; interviews, on-line survey and discussion forums.The interpretative analysis technique was used to analyze the data and the results were produced based on the analysis. This paper contributes to our understanding the personality factors of teleworkers success in balancing work and home life.The results show that factors such as time management, discipline, family support , motivation, and patience are important in managing work and family while working from home.